ACCOUNTING OUTSOURCING IN MODERN CONDITIONS OF RUSSIAN ECONOMY - O. Vishnyakova; Z. Korzovatykh (Вестник университета, 2016)
The article analized the features of accounting outsourcing in organizations, the positive and negative sides of transition of Russian companies to this type of accounting.